Features of Remote Work in Ukraine and the European Union: Comparative Legal Aspect - Yaroshenko, Oleg; Melnychuk, Nataliia; Moroz, Sergiy; Havrylova, Olena; Yaryhina, Yelyzaveta (Hasanuddin Law Review, 2021)
The relevance of the study is based on the development of scientific and technological progress and the expansion of the labor market, including in the framework of international cooperation. Moreover, the introduction of quarantine due to the spread of Covid-19 has led to increased attention to remote work. The aim of the study is to analyze the legal aspects of remote work in accordance with the labor legislation of Ukraine and the European Union, focusing on the concept of remote work, the rights and obligations of remote workers. In our study, we determined that in the European Union, the key points in relation to the rights granted to teleworkers, which the countries parties to the agreement have undertaken to incorporate into their national legislation and collective agreements, are data protection; the voluntary nature of telecommuting; equipment; organization of working time; privacy. The originality of the study is based on more effective ways to improve labor productivity in Ukraine, labor discipline, compliance with labor guarantees for remote work. It is necessary to revise and legislatively regulate the key principles of compliance by employees with labor discipline, providing the employee with proper working conditions, supporting the employer in search of new opportunities to provide employees with work, improving the technical aspects of ensuring the relationship between business and government, responsibility for results and the labor process.